Effects of Suspended Sediment on Early-Life Stage Survivalof Yaqui Chub, an Endangered USA–Mexico Borderlands Cyprinid - Clark Barkalow, Stephani L; Bonar, Scott A (Transactions of the American Fisheries Society (1900), 2015)
High levels of total suspended sediment (TSS) can have negative consequences on fishes, such as altering food supply, lowering food acquisition, clogging gills, and disrupting reproduction. While effects of TSS on salmonids and estuarine fish are well studied, less is known about possible negative impacts of suspended sediment on desert fishes. Several imperiled desert fishes inhabit streams and springs near the U.S.–Mexico border and are potentially threatened by increased sediment loads from borderlands activity such as livestock grazing, road building, illegal traffic, and law enforcement patrols. One such species is the Yaqui Chub Gila purpurea, a federally listed endangered cyprinid. We exposed Yaqui Chub embryos and fry (mean TL = 12.6 mm; SE = 0.42) to a range of TSS levels commonly found in one of the only streams they inhabit, Black Draw, which crosses the Arizona–Mexico border. We tested effects of 0; 300; 500; 1,000; 5,000; and 10,000 mg/L TSS loads on fry and embryos over a 5-d period in three replicate containers for each treatment. Fifty percent hatch rate (i.e., median lethal concentration, LC50) was 3,977 mg/L for embryos. The LC50 for fry (concentration at which half died) was 8,372 mg/L after 12 h of exposure; however, after 5-d exposure, LC50 leveled at 1,197 mg/L. The TL of fry did not change significantly in any treatment over the 5-d period. Suspended sediment in Black Draw reached concentrations lethal to Yaqui Chub embryo and fry during four floods in 2012. Although some desert fishes have evolved in rivers and streams subject to elevated TSS and are tolerant to high TSS concentrations, other fish species are less tolerant and may be impacted by land practices which increase erosion into stream systems. Management of critically endangered desert fishes should include considerations of the effects of increased suspended sediment. Received September 5, 2014; accepted November 10, 2014